Qualidade da atenção ao pré-natal e parto no Rio Grande do Norte: chamada neonatal, 2010 - Silva, Adriana Souza da (2013)
A cross-sectional study was carried out based on data originated from the national survey "Chamada Neonatal, 2010". This study aimed to evaluate the quality of prenatal and childbirth care offered to pregnant women in Rio Grande do Norte (RN) according to criteria established by the Ministry of Health (MOH). The sample consisted of 837 pairs, mother and child under one year old, which responded to the survey at the 9 priority cities for the Pact for the Reduction of Infant Mortality in the state. A descriptive analysis of data for complex samples was made. The results show low proportion of adequate prenatal care (4.8%), the prevalence of partially adequate (50.2 %) and 45 % of inadequacy. Among the components of prenatal most affected are: making and receiving exams at the appropriate time, receive guidance on breastfeeding and on the place of the childbirth and implementation of breasts examination. The results to labor show an adequate under 1%, 56.9% of inadequacy and 42.4% of partially adequate. The criteria most affected are: birth where indicated, family support for women during and waiting period for admission. Even so, the mother's opinion in relation to prenatal and childbirth care was good or very good in over 80% of the interviews. It is noticed that, in general, this framework helps to contribute to the maintenance of maternal and child mortality in the region, and that even with improved access the health services, managers and health professionals need to be better prepared to offer to pregnant women accompaniment according to recommending by Ministry of Health and its programs and politics.